Responses of Vitis vinifera L. cv. Sultanina to Water Deficits During Various Pre- and Post-Harvest Phases Under Semi-Arid Conditions - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
Performance of Sultanina grapevines irrigated at 60% plant-available water depletion (Tl) were compared to situations where water deficits were induced at budbreak (T2), before flowering (T3), after flowering (T4), at pea size (TS) and during ripening (T6). The field trial was performed on a fine sandy soil at Upington in the Lower Orange River region in South Africa. Treatments Tl to T6 were irrigated at 60% plant-available water (PAW) depletion during the post-harvest period and winter. A further four treatments were irrigated at 60% PAW depletion from budbreak until irrigation was terminated three weeks (T7), seven weeks (TS), eleven weeks (T9) and fifteen weeks (TlO) after harvest, respectively. The periods of water stress induced during the various pre-harvest phenological phases were too short to have a significant effect on vegetative growth. Water deficits during the early season (T2, T3 and T4) tended to affect yield more negatively than deficits applied between pea size and harvest (TS and T6).  Yield reduction was associated with tendencies toward reduced bunch differentiation, berry shed and smaller berries. Berry size was significantly reduced by water deficits induced after flowering (T4). Water deficits had no significant effect on juice sugar content or on total titratable acids. No choice-grade sun-dried raisins could be produced when grapevines were subjected to water deficits during ripening (T6). In comparison to continued irrigation at 60% PAW depletion and water deficits induced up to pea size, significant browning of dipped raisins produced from TS and T6 grapevines occurred during some seasons. In combination with low relative humidity, water deficits between pruning and budbreak (T7 to TlO) reduced yields significantly compared to continued irrigation at 60% PAW depletion throughout the post-harvest period. Low relative humidity and dry soil also induced delayed budbreak and stimulated excessive shoot growth after harvest to such an extent that cane mass was significantly higher compared to irrigation at 60% PAW depletion. Neither water deficits nor significant shoot regrowth during the post-harvest period had any effect on cane starch content at pruning.